Jürg Frey, String Quartet no. 4. Quatuor Bozzini. MaerzMusik live-stream, 25 March 2021. (October 2021) - Power, Ian
Abstract : Jürg Frey is at the point where the premiere of his String Quartet no. 4 at the online edition of MaerzMusik this March had the feel of the release of the newest film from a cult director. For my generation, this has largely meant someone like Quentin Tarantino or the Coen Brothers: every two to four years a new movie with sameness (recurring actors) and differences (genre) comes out, and with it a new opportunity to spend an interval of time with something carefully crafted by a unique mind with one foot in the real world and one foot out of it. We dutifully check them out, interested not just in the 'next big thing' but also in the moment surrounding this bit of culture.